'A Different Ball Game': Adaptation of a men's health program for implementation in rural Australia - Matthew D. McDonald; Kate Hunt; Joanna Moullin; Deborah Kerr; Nikos Ntoumanis; Eleanor Quested (BMC, 2023)
Abstract Background Men residing in rural areas are less likely to participate in weight management interventions than women, and few men-specific programs target rural areas. Aussie-Fans in Training (Aussie-FIT) is an evidence-based weight management intervention that uses professional Australian Football club affiliations and settings as a 'hook' to engage urban-residing men. The aim of this study is to report on how findings from rural stakeholder focus groups were used to inform the adaptation of Aussie-FIT for implementation in rural areas. Methods Seven focus groups with stakeholders (n = 24) in three rural towns explored existing weight management and physical activity provisions, barriers and facilitators to engaging men, and considerations for adapting Aussie-FIT for implementation in rural contexts. Qualitative data were analysed using the framework approach. Adaptations made to the Aussie-FIT program and strategies to implement the program in rural contexts were reported using a structured framework. Results Themes generated from our analysis include limited appealing services for men, Australian Football as a 'common language', the influence of the 'smaller fishpond'(population), considerations for program inclusivity, and the importance of local partner organisations for sustainability. We adapted the recruitment and marketing strategies, delivery settings, football program theme and partnerships for rural implementation. Stakeholders advised that an Australian Football program theme without specific local club affiliations would be important to avoid alienating men with differing club allegiances or non-sporting backgrounds. A multi-component recruitment strategy utilising local trusted sources, and program marketing that aligns with masculine ideals were considered important by stakeholders in small communities where 'people talk'. Conclusions Rural areas were described as 'a different ball game' due to limited local services and resources in comparison to metropolitan areas. Study findings have synergies with previous studies undertaken in rural contexts including in relation to the power of word of mouth, the importance of trust, and local partner organisations. Findings have implications for engaging rural men in health interventions in rural contexts where professional sporting contexts are not available. Assessing the extent to which the adapted Aussie-FIT program can reach and engage men in rural Australia, and exploring the barriers and facilitators to delivering the program in rural contexts is required.